2010
DOI: 10.2478/v10046-011-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic aspects of chronic low back pain syndrome

Abstract: Psychosomatic aspects of chronic low back pain syndrome The purpose of the study was to determine the relationships between emotional distress and pain syndrome, its characteristic parameters and impact on the quality of life in patients with chronic low back pain. The study included 110 patients, mean age 44.2 ± 8.0 years, with clinical diagnosis of lumbar spine disk pathology with chronic low back pain syndrome. The results showed that the studied patients differed by their emotional state. Emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…There were only few studies that confirm concurrent action of pain and proprioception stimulus in spinal cord level ("gate control mechanism") [18,31], that could partly explain our findings. In addition, previous studies have found close relationship between pain intensity and anxiety in chronic back pain patients [33], thus it can be presumed that anxiety and fear were the main mediators between higher pain intensity and greater joint position sense impairment. For patients with chronic back pain the component of somatization and fear (especially fear of movements) has been observed already in previous studies [33].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There were only few studies that confirm concurrent action of pain and proprioception stimulus in spinal cord level ("gate control mechanism") [18,31], that could partly explain our findings. In addition, previous studies have found close relationship between pain intensity and anxiety in chronic back pain patients [33], thus it can be presumed that anxiety and fear were the main mediators between higher pain intensity and greater joint position sense impairment. For patients with chronic back pain the component of somatization and fear (especially fear of movements) has been observed already in previous studies [33].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, previous studies have found close relationship between pain intensity and anxiety in chronic back pain patients [33], thus it can be presumed that anxiety and fear were the main mediators between higher pain intensity and greater joint position sense impairment. For patients with chronic back pain the component of somatization and fear (especially fear of movements) has been observed already in previous studies [33]. Our finding in the relationship between pain intensity and joint reposition error in limb adjacent to pain localization could be mainly explained by fear and excessive awareness of the painful site (back part), which could result in poor motor task performance (e.g.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Working with computers presents ergonomic risks due to the static postures that are maintained for a long time; they are repetitive and sometimes forceful (Nag et al, 2009;Zakerian and Subramanian, 2009;Brauer et al, 2010;Mueller and Hassenzahl, 2010;Ðmite and Ancane, 2010). The overuse syndrome caused by physical overload includes common lesions such as channel bursitis, mono-and polyneuropathies, and compression (Orsila et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The emotional side of a person and the physical side are closely connected (Ðmite and Ancane, 2010); low back pain as a musculoskeletal disorder (MSD) is associated with the physical and emotional factors.…”
Section: Introductionmentioning
confidence: 99%